ANALYSIS OF THE INFLUENCE OF VILLAGE FUNDS, CAPITAL EXPENDITURES, AND TAX REVENUE SHARING ON VILLAGE INFRASTRUCTURE DEVELOPMENT WITH RETRIBUTION AS AN INTERVENING VARIABLE (STUDY IN BETEKTAMAN VILLAGE, GADING DISTRICT, PROBOLINGGO) - Sujatmoko, Timbul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of village funds, capital expenditures, and tax revenue sharing on village infrastructure development, with retribution serving as an intervening variable. The research focuses on Betektaman Village in Gading District, Probolinggo, providing a detailed evaluation of financial factors and their role in enhancing rural infrastructure. Method: The study employs a quantitative approach, utilizing data collected through documentation, financial reports, and other relevant sources. Path analysis was conducted to assess the direct and indirect relationships between the independent variables (village funds, capital expenditures, and tax revenue sharing) and the dependent variable (village infrastructure development), with retribution acting as the intervening variable. Results: The findings reveal that village funds, capital expenditures, and tax revenue sharing significantly impact infrastructure development in Betektaman Village. Moreover, retribution partially mediates these relationships, indicating its role as a crucial factor in the effective allocation and utilization of financial resources. Novelty: This study contributes to the existing body of knowledge by integrating retribution as an intervening variable, providing a nuanced understanding of its mediating effect on financial resource utilization for village infrastructure. It highlights the importance of optimizing financial allocation mechanisms to ensure sustainable rural development.